Remote Monitoring of COVID-19 Patients Using Multisensor Body Area Network Innovative System - Al-Barazanchi I.; Hashim W.; Ahmed Alkahtani A.; Rasheed Abdulshaheed H.; Muwafaq Gheni H.; Murthy A.; Daghighi E.; Shawkat S.A.; Jaaz Z.A. (Hindawi Limited, 2023)
Cryptography; Health care; Health risks; Hospital data processing; Internet protocols; Viruses; Bodyarea networks (BAN); Health industry; Healthcare systems; Healthcare workers; Innovative systems; Multi sensor; Patient data; Public safety; Remote monitoring; Well being; Intelligent systems